(untitled) (Bioremediation Science and Technology Research (e-ISSN 2289-5892), 2019)
Pollution of the environment by heavy metals and other toxic xenobiotics has increasingly become global public health concern. Bacterial reduction of molybdenum to insoluble molybdenum blue (Mo-blue) forms the basis for its bioremediation. A bacterium with the ability to reduce toxic soluble molybdenum has been isolated from Agricultural soil and identified as Pseudomonas sp. based on the 16S rRNA partial sequencing and phylogenetic analysis. Spectroscopic analysis reveals that the bacterium reduced sodium molybdate to Mo-blue optimally at pH between 6.5 and 7.0, temperatures between 35 Â°C and 40 Â°C. Glucose was the best electron donor source supporting molybdate reduction, followed by sucrose, fructose, glycerol and starch in descending order. Other requirements include a phosphate concentration of 3.5 mM and a molybdate concentration of between 40 and 60 mM. The absorption spectrum of the Mo-blue produced was similar to the previously isolated Mo-reducing bacteria and closely resembles a reduced phosphomolybdate.